Knowledge and barriers of incident report among nurses in teaching hospital, Bharatpur - Lama, Sajina; Khanal, Dina (Journal of Chitwan Medical College, 2021)
Background: An incident report is a formal recording of the facts related to a workplace accident, injury or near miss. So, incident should be reported properly and immediately in effective way which would lead appropriate management and prevention of incident. This study aimed to assess the knowledge and barriers of incident reports among nurses. Methods: A cross-sectional study design was used among nurses working in teaching hospitals. A simple random sampling technique was used to select 208 nurses and data was collected by using self-administered questionnaire from June 18, 2019 to July 18, 2019. Data was analyzed in SPSS version 20 using descriptive statistics and inferential statistics. Results: This study revealed that 73.1% of respondents had poor knowledge on incident report. Whereas common barrier identified by respondents were work complexity (40.4%), fear of blamed (59.1%), lack of protocol (50.0%) and inadequate reporting system (42.3%). Nurses level of knowledge was statistically significant with level of education (p=0.001), professional designation (p=0.001), available guideline (p=0.004) and available reporting format (p=0.014) Conclusions: This finding concluded that nurse’s knowledge is limited on incident reports and number of barrier of incident reporting had been identified. With this information nurses knowledge should be upgraded by providing in service education on incident report and availability of protocol along this hospital administrator should support, ensure anonymity and create a strong safety culture within hospital which will reinforce staff to report incident immediately thus to reduce the reoccurrence of errors and enhance patient’s safety.